Preliminary evidence of a reduced serum level of fibroblast growth factor 19 in patients with biopsy-proven nonalcoholic fatty liver disease - EREN, FATİH; ATUĞ, ÖZLEN; YILMAZ, YUSUF (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Objectives: We sought to determine whether serum concentrations of fibroblast growth factor 19 (FGF19) - an ileum-derived enterokine which plays a role in the control of glucose and lipid homeostasis - are altered in patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD). Design and methods: Serum levels of FGF19 were measured using enzyme-linked immunosorbent assay in 91 patients with biopsy-proven NAFLD and 74 controls. Results: FGF19 levels were significantly lower in patients with biopsy-proven NAFLD (median: 130 pg/mL) than in controls (median: 210 pg/mL, P<0.001). Serum FGF19 levels were significantly but modestly associated with hepatocyte ballooning scores in univariate analysis (r = -0.25. P<0.05) but not after adjustment for potential confounders (beta = -0.18; t = 1.78, P = 0.08). Conclusions: This pilot study suggests that serum FGF19 levels are decreased in patients with NAFLD but are not independently associated with liver histology findings. (C) 2012 The Canadian Society of Clinical Chemists. Published by Elsevier Inc. All rights reserved.
Keywords: Fibroblast growth factor 19; Nonalcoholic fatty liver disease; Hepatocyte ballooning; Enzyme-linked immunosorbent assay; INSULIN-RESISTANCE; METABOLIC SYNDROME; FGF19; STEATOHEPATITIS; MICE